Strengthening Mental Health for Adolescents in Orphanages Through the Role of Self-Disclosure and Self-Compassion - Nur , Akbar; Rahmatullah , Azam Syukur; Khilmiyah , Akif (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Adolescence is a transition from childhood to adulthood, along with problems resulting in mental health. Therefore, parental assistance is required. However, teenagers living in orphanages have different life paths as they do not get as much affection as those with parents. Having self-disclosure and self-compassion may help tackle mental health problems. This study aimed to analyze the role of self-disclosure and self-compassion on adolescents’ mental health in orphanages and determine the causes and solutions. The research used the mixed method with 43 samples of teen orphans aged 12-18 taken from the Daarut Taqwa Orphanage, Minggir, Sleman, Yogyakarta, Indonesia. Data collection techniques used interviews, observations, and research questionnaires. Qualitative data analysis used reduction, display, and conclusion techniques, while the quantitative data analysis using multiple linear regression. The results showed an effect of self-disclosure of 19.7% and the effect of self-compassion of 21.9% on the teen orphans’ mental health. The other 58.4% were other factors such as upbringing, environment, and education. The multiple linear regression test results showed the effect of self-disclosure and self-compassion of 23%. Factors affecting the mental health of orphanage youth included the family background, e.g., families of domestic violence victims, victims of pornography and poor parenting. Strengthening mental health for orphanage adolescents can be done by instilling a consistent attitude of self-disclosure and self-compassion.